An Historical Overview of the Culture of Sports in Indonesia: Global Issues and Challenges for Future Indonesian Sports Development Policies. Issue 2 (4th May 2022) - Ma'mun, Amung; Anggorowati, Rita; Risma, Risma; Slamet, Suherman; Anira, Anira
Abstract: This article seeks to scrutinize the practices involved in promoting sport and exercise culture in Indonesia from a historical perspective and its relationship to global issues. It is expected to give rise to new ideas and advancements for the future developments of sports culture. The promotion is divided into several phases from far before the colonial era. The concept of sport and exercise development surfaced in Indonesia in 1984-1985 in the wake of the UNESCO'78 declaration on sports and physical education. Sport has recently come to colour Indonesia's national sports development policies in response to global issues. Elite sports have attained a central position in promoting the nation's honour, image, and dignity through competition against peer states. Meanwhile, sport and exercise development concepts related to the pursuit of MDGs (Millenium Development Goals) and SDGs (Sustainable Development Goals) under the UN concept of SDP (Sport for Development and Peace) have not become a prominent strategic issue. They thus have not attracted enough attention to become a routine element of the government policy. This paper will engage in a detailed discussion of new ideas for the future evolution of Indonesian policies in the development of sport and physical exercise to achieve Indonesia's national ideals as stated in the Preamble of the Indonesian 1945 Constitution.